2018
DOI: 10.19045/bspab.2018.70048
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability estimates for yield and fibre quality traits in Bt and non-Bt upland cotton genotypes

Abstract: , lint %, staple length and fibre fineness were evaluated. The male × female interaction's significant differences clearly indicated the importance of specific combining ability (SCA) of hybrids and proposed the dominant genes involvement in the articulation of studied characters. The significant mean squares owing to both female and male parents determined the general combining ability (GCA) indicated predominant effect of the additive variances advocating the studied parameters. Higher values of σ 2 SCA agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…By exploiting this cross the best transgressive segregants for yield, other yield contributing traits and fibre quality parameters can be selected in further generations. Similar results were also recorded by Preetha and Raveendran (2008), Palve (2009), Hussain et al, (2010), Khan et al, (2015), Sawarkar et al, (2015), Solanki et al, (2015), Usharani et al, (2016), Babu et al, (2017), Monicashree et al, (2017), Anjum et al, (2018) and Munir et al, (2018). Similarly, the hybrid AKH 84635 x SURAJ exhibited positive and significant sca effects for seed cotton yield (12.96).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…By exploiting this cross the best transgressive segregants for yield, other yield contributing traits and fibre quality parameters can be selected in further generations. Similar results were also recorded by Preetha and Raveendran (2008), Palve (2009), Hussain et al, (2010), Khan et al, (2015), Sawarkar et al, (2015), Solanki et al, (2015), Usharani et al, (2016), Babu et al, (2017), Monicashree et al, (2017), Anjum et al, (2018) and Munir et al, (2018). Similarly, the hybrid AKH 84635 x SURAJ exhibited positive and significant sca effects for seed cotton yield (12.96).…”
Section: Resultssupporting
confidence: 73%
“…Thus, above promising male parents having high gca effects for seed cotton yield, yield related traits and fibre parameters can be suitably used in the hybridization programmes over the environments under study for improvement of individual trait per se. The high gca effects among males and females for seed cotton yield, its components traits and fibre quality parameters have also been reported by other workers viz., Pavasia et al, (1999), Dheva et al, (2002) Ahuja and Dhayal (2007), Dhamayanthi et al, (2008), Palve (2009), Saravanan et al, (2010), Alkuddsi et al, (2013, Sawarkar et al, (2015), Usharani et al, (2016), Monicashree et al, (2017) and Anjum et al, (2018).…”
Section: Resultsmentioning
confidence: 99%
“…These findings were consistent with (Hussain et al, 2008 and2009;and Patel et al, 2014).The results of proportional contributions % showed that lines, testers and the interaction lines × testers brought many variations in the expression of the studied traits. These findings were consistent with (Anjum et al, 2018;and Yehia and El-Hashash, 2019;and different from Hamed and Said, 2021;and Mariz et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Selection based on seed yield and its components should be based on genotypic variance and the proportion of the genetic gain and heritability for each trait (El-Hashash and Agwa, 2018). In this context, several researchers like (Khan et al, 2009;El-Hashash, 2013;Anjum et al, 2018;Hamed and Said , 2021;and Mariz et al, 2021) have reported that the majority of genetic variances of yield, its components and fiber quality traits are under the control of non-additive nature of genes.…”
Section: Introductionmentioning
confidence: 99%
“…So parent's selection for hybridization can be done because of combining ability and per se performance. However, the effects of gca and sca are more informative and reliable than per se values as they also provide information about the type of gene action; that is, additive or non-additive (Anjum et al, 2018, Richika et al, 2021and Gnanasekaran and Thiyagu, 2021. The primary objective of the breeding programme is to improve seed cotton yield that has low heritability which is highly affected by genotype×environment interaction.…”
Section: Introductionmentioning
confidence: 99%